Cultural tensions – exploring call centres in the public sector. (19th July 2006) - Anderson, Eve; Pyman, Amanda; Teicher, Julian
The mostly private sector literature on call centre work suggests two distinct images: electronic sweatshops and customer focus (Deery and Kinnie, 2002). In the public sector, call centres have become widespread as governments import private sector management practices. Under the rubric of New Public Management (NPM), contestability and client focus require call centres and other public services to compare or at least benchmark against the private sector. However, the limited literature on public sector call centres highlights distinctive features of the sector along with the pervasiveness of private sector operational and managerial practices. This paper explores the cultural tensions between traditional public sector work organisation and the marketisation of public services through case studies of call centres in two large Australian government agencies. This discussion is organised around the themes of the characteristics and tensions of the call centres, the organisation of work, and the management of the employment relationship.